The Arabidopsis Lectin Receptor Kinase LecRK-I.8 Is Involved in Insect Egg Perception - Gouhier-Darimont, Caroline; Stahl, Elia; Glauser, Gaetan; Reymond, Philippe (Frontiers in Plant Science, 2019)
Plants induce defense responses after insect egg deposition, but very little is known about the perception mechanisms. In Arabidopsis thaliana, eggs of the specialist insect Pieris brassicae trigger accumulation of reactive oxygen species (ROS) and salicylic acid (SA), followed by induction of defense genes and localized necrosis. Here, the involvement of the clade I L-type lectin receptor kinase LecRK-I.8 in these responses was studied. Expression of LecRK-I.8 was upregulated at the site of P. brassicae oviposition and egg extract (EE) treatment. ROS, SA, cell death, and expression of PR1 were substantially reduced in the Arabidopsis knock-out mutant lecrk-I.8 after EE treatment. In addition, EE-induced systemic resistance against Pseudomonas syringae was abolished in lecrk-I.8. Expression of ten clade I homologues of LecRK-I.8 was also induced by EE treatment, but single mutants displayed only weak alteration of EE-induced PR1 expression. These results demonstrate that LecRK-I.8 is an early component of egg perception.